Case Report: Congenital Arthrogryposis and Unilateral Absences of Distal Arm in Congenital Zika Syndrome - Contreras-Capetillo, Silvina Noemí; Palma-Baquedano, José Rafael; Valadéz-González, Nina; Manrique-Saide, Pablo; Barrera-Pérez, Hirian Alonso Moshe; Pinto-Escalante, Doris; Pavía-Ruz, Norma (Frontiers in Medicine, 2021)
Zika virus was recognized as a teratogen in 2015, when prenatal Zika infection was associated with neonatal microcephaly. The transmission, virulence, tropism and consequences of Zika virus infection during pregnancy are currently studied. Decreased neural progenitor cells, arrest in neuronal migration and/or disruption of the maturation process of the fetus central nervous system have been associated. Congenital Zika Syndrome produces a fetal brain disruption sequence resulting in structural brain abnormalities, microcephaly, intracranial calcifications, fetal akinesia and arthrogryposis. Vascular abnormalities like unique umbilical artery and decreased cerebral vascular flow have been described in some patients. This article reports a Zika positive patient with sequence of fetal brain disruption, arthrogryposis and absence of distal third of the right forearm. This report expands the clinical observations of congenital Zika syndrome that may be related to disruptive vascular events.